On analytic solutions of the equation ϕ(f(x)) = g(x,ϕ(x)) (III) - Ger, Joanna (Annales Mathematicae Silesianae, 1985)
In the present paper we deal with local analytic solutions of the functional equation announced in the title. This paper is a continuation of [2] and [3].